EFFECTIVENESS OF REGIONAL POLITICAL ORGANIZATIONS IN INTERNATIONAL RELATIONS IN THE CONTEXT OF GLOBALIZATION - CHISTIAKOVA, Iryna; Babina, Valentyna (Fìlosofìâ ta polìtologìâ v kontekstì sučasnoï kulʹturi, 2024)
This article examines the impact of globalization on the development and functioning of regional political organizations in international relations. It analyses the effectiveness of regional political systems amidst globalized processes, focusing on mechanisms of interaction and coordination that contribute to regional stability and development. The study also identifies key challenges and threats these organizations face in the context of globalization. Additionally, the research aims to develop recommendations for enhancing the efficiency of regional political systems through optimizing existing cooperation and integration strategies.The study adopts an interdisciplinary approach, incorporating analysis of historical development of regional political systems, examination of contemporary political and economic processes, and analysis of specific activities of key regional organizations. The relevance of the study is underscored by the necessity to understand the effectiveness of regional political organizations in addressing global challenges. The scientific novelty lies in the comprehensive analysis of the interaction between regional organizations and global structures, emphasizing their role in contemporary international relations. The research highlights the role of regional political organizations as intermediaries between national states and global structures. It identifies these organizations as facilitators in conflict resolution, economic integration, and stability. The study assesses both positive and negative aspects of globalization for regional political organizations, along with the challenges they encounter.Practical implications of this work include providing recommendations to enhance the effectiveness of regional political organizations in a globalized world. These recommendations are valuable for policymakers, analysts, and international organizations engaged in regional cooperation and global governance. The article significantly contributes to understanding the role of regional political organizations in the contemporary international landscape, emphasizing their importance in addressing global issues and ensuring international stability. The findings of the study open new perspectives for further research and development of management strategies in these contexts.